Trees in Patagonia - Gut, Bernardo (Birkhäuser Basel : Imprint: Birkhäuser, 2008)
This book is a guide to the native trees and approximately 95% of the introduced arboreal species of Argentine and Chilean Patagonia. Introductory chapters convey an overview on what is termed 'Patagonia', as well as on the geology, climate, soils, and vegetation of Southern South America. Keys based on vegetative characters and richly illustrated descriptions of more than 170 species form the core of the manual. These chapters are followed by concise entries on afforestations, urban trees, and plantations of fruit trees in climatic enclaves. Renowned experts describe the most important National Parks of both Argentine and Chilean Patagonia. The last chapter is devoted to Carl Skottsberg and his remarkable expedition through Patagonia a hundred years ago.